Spectrum of complaints: practices of complaining in therapeutic conversations as a window to spouses' personalities and couples' relationships - Taurogiński, Bartłomiej; Janusz, Bernadetta; Bergmann, Jörg R.; Peräkylä, Anssi (Frontiers in Psychology, 2023)
Complaining is a frequent phenomenon in human interactions. We used conversation analysis to explore the interactional organization of complaining in the specific context which is couple's therapy. A conversation between a therapist and spouses that requires them to talk about problems inevitably leads to complaining (especially during the first meeting). The institutional context and the presence of an impartial therapist shape the complaining sequences. Our data involves video recordings of 9 couple therapy first consultations. In the data analysis, we describe in detail the composition and delivery of complaints in this setting. Our observations made it possible to propose a nuanced spectrum of ways of complaining that spans the considerateness dimension. Our data suggest that there may be a relationship between the manner of complaining and the presence and severity of maladaptive personality traits of complainers. We argue that paying close attention to complaining practices that arise during couple therapy is an important aspect of clinical work with couples and can be informative in terms of nature of spouses quarrels but also their personality constitutions.